Impact Of Roof Surface Material On Rainwater Runoff Quality In Public University - Iona Evinna Khanching, Geruka (2025)
The quality of rainwater runoff is greatly influenced by the type of roofing material used in buildings, especially in institutional contexts like college campuses. This study examines how various roof surfaces affect the rainfall runoff's water quality at the University Malaysia Pahang Al-Sultan Abdullah (UMPSA) campus in Gambang. This study investigates the connection between roofing materials, rainfall characteristics, and water quality with a focus on three significant locations: the Student and Alumni Affairs Department (polycarbonate), Payung Putih Café (zinc), and Student Resident 1 (concrete tiles). In order to assess important water quality parameters such as pH, total suspended solids (TSS), chemical oxygen demand (COD), total phosphorus (TP), total nitrogen (TN), and heavy metals, rainwater runoff samples were collected during rainstorm episodes using an experimental technique. The National Water Quality Standards (NWQS) of Malaysia were followed in the performance of these studies. The results show that roofing materials have a big impact on water quality. Concrete tile roofs showed neutral pH (6.65-6.94) and pristine quality within NWQS Class I. Zinc roofs exhibited significant zinc pollution, with concentrations up to 164.29 mg/L, exceeding the Class III limit (<5 mg/L), and localized copper contamination (0.21 mg/L). Polycarbonate roofs had minimal COD levels (0.00 mg/L) due to their smooth surface, reducing pollutant adhesion. The TSS values across all roof types ranges from 814.6–942 mg/L, influenced by rainfall intensity and antecedent dry weather periods and significantly exceeding the NWQS Class V of 300 mg/L. TP levels occasionally exceeded the NWQS Class III limit (0.2 mg/L) for polycarbonate and concrete tile roofs, with the highest levels observed after prolonged dry periods and heavy rainfall, while zinc roofs showed no TP contamination TN was consistently undetectable across all roofing materials, indicating no nitrogen pollution in the runoff. Concrete tiles showed varying rainfall intensities (3.75×10-7 to 4.04×10-6) with dry periods of 2 to 4 days, zinc roofs had intensities from 4.25×10-6 to 1.38×10-6 after 2 to 5 days of dry weather, and polycarbonate roofs had intensities between 6.27×10-7 and 2.46×10-6 with dry periods of 1 to 3 days. Furthermore, the study determines the pollution levels of rainwater runoff in reference to the National Water Quality Standards (NWQS) of Malaysia, identifying compliance and areas of concern, such as significant heavy metal pollution on zinc roofs and elevated TSS levels across all roof types. This study gives policymakers and university administrators important direction for enhancing campus water quality and promoting sustainable rainwater management by offering evidence-based ideas. In addition to addressing the study's goals, the results add to a larger conversation on environmental sustainability and urban water quality management.